Control and Simulation Optimization of Electromagnetic Noise for Locomotive Transformer - Yongsheng WANG; Jie DING; Liang XIA; Yaping ZENG; Xiaobin ZANG; Zhenpeng LI (机车电传动)
It was found that the electromagnetic noise of a certain transformer of a locomotive on site was prominent, resulting in harsh screech, which seriously affects hearing. In view of this phenomenon, the acoustic tests of electromagnetic noise of transformer were carried out in the field and workshop to study the acoustic characteristics, based on which the optimization scheme of acoustic packaging was put forward according to the actual installation condition and sound propagation characteristics of the transformer, and the acoustic simulation calculation and experimental verification of the optimization scheme were carried out. The results showed that the optimized scheme could significantly improve the electromagnetic noise performance of the transformer and the riding comfort with low cost.